Nothing is impossible : America's reconciliation with Vietnam - Osius, Ted (Rutgers University Press, 2022)
"Today Vietnam is one of America's strongest international partners, with a thriving economy and a population that welcomes American visitors. How that relationship was formed is a twenty-year story of daring diplomacy and a careful thawing of tensions between the two countries after a lengthy war that cost nearly 60,000 American and more than two million Vietnamese lives. Ted Osius, former ambassador during the Obama Administration, offers a vivid account, starting in the 1990s, of the various forms of diplomacy that made this reconciliation possible. He considers the leaders who put aside past traumas to work on creating a brighter future, including senators John McCain and John Kerry, two Vietnam veterans and ideological opponents who set aside their differences for a greater cause, and Pete Peterson-the former POW who became the first U.S. ambassador to a new Vietnam. Osius also draws upon his own experiences working first-hand with various Vietnamese leaders and traveling the country on bicycle to spotlight the ordinary Vietnamese people who have helped bring about their nation's extraordinary renaissance. With a foreword by former Secretary of State John Kerry, Nothing is Impossible tells an inspiring story of how international diplomacy can create a better world"--